Getting beyond forced technology transfers analysis of and recommendations on intangible economy governance in China - Anton Malkin (Centre for International Governance Innovation (CIGI), 2020)
What role does the Chinese government play in the acquisition of foreign technology by Chinese firms, both state-owned and private? The answer is seemingly straightforward, or so the US government contends: intellectual property (IP) theft and industrial espionage, coupled with market leverage to extract foreign technology from foreign direct investment arrangements - so-called forced technology transfers. Challenging these perceptions, this paper takes a closer look at the drivers of Chinese firms' technology acquisition from three dimensions. It finds that - paradoxically - as accusations of China's illicit or state-driven acquisition of technology reach a fever pitch, China's domestic and outbound technology acquisition regime, as well as its IP system more broadly, is becoming more formalized, predictable and rules-driven. Policy makers and firms with significant intangible asset portfolios should prepare for a not-too-distant future when technology transfer flows from, not just into, China.
Keywords: 330